BIOSORPTION OF METHYLENE BLUE FROM WASTE WATER USING LEBANESE CYMBOPOGON CITRATUS (CITRONNELLE) - Akram Hijazi; Ali Mcheik; Hassan Rammal; Wassim Rammal; Houssein Annan; Joumana Toufaily; Tayssir Hamieh (European Scientific Journal, ESJ, 2015)
The objective of this study was to investigate the possibility of using Lebanese Cymbopogon citratus stem as an alternative adsorbent for the removal of methylene blue from aqueous solutions. Different parameters such as the effect of initial concentration, pH, adsorbent dose, contact time and temperature were studied. Maximum adsorption capacity (61%) of MB was obtained at PH=6 an initial concentration 200 mg/L after 24h and at 25 ˚C. The adsorption isotherm was better described by a Freundlich model rather than a Langmiur model. Based on these results, it can be concluded that the stems of Cymbopogon citratus is effective as an alternative adsorbent for MB remediation in waste water.